BREAD PRODUCTION PROCESS AT JASUN BAKERY UMKM IN SUKABUMI CITY - Herny Nurhayati; Ardelia Septhiani Lasalina (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Management originates from the word "to manage" which means to control or regulate. Management, as a process of managing resources to achieve goals, is the foundation for understanding the importance of production process management. The production process itself is a series of activities that transform raw materials into finished products. This study focuses on analyzing the bread production process at Jasun Bakery Sukabumi City. The aim of this study is to identify the challenges faced in the bread production process and to find solutions to overcome them. The research method used in this study is a qualitative research method, an approach in conducting research that is oriented toward natural phenomena or events. Based on the results of the research conducted at Jasun Bakery Sukabumi City, it is found that the selection of raw materials should be done more carefully, the baking process should be more closely monitored, and the management of raw material inventory should be improved. Thus, it is expected that the quality of bread products can be improved and production efficiency can be achieved. There are several main challenges at Jasun Bakery Sukabumi City, namely the less careful selection of raw materials, the lack of supervision in the baking process, and problems with raw material inventory.